(untitled) (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2023)
The definition of the southwestern territory of the Iberians has been a topic of discussion since the Turdetans considered themselves a cultural group differentiated from them. In this paper, some of their analysis fronts will be contrasted: linguistic, historical and archaeological, taking as reference the stratigraphy of the territory. At the same time, the difference between the cultural limit and the border will be valued following the political process defined by the oppida among the southern Iberians.